Processamento sensorial e áreas da checklist de triagem de desenvolvimento/comportamento de crianças em jardins de infância - Palma, Sónia (2015)
Submitted by Alexandra Guerreiro (alexandra.guerreiro@essa.pt) on 2015-09-01T16:13:56Z No. of bitstreams: 3 Tese definitiva 2015 rect.pdf: 499714 bytes, checksum: d0fb82a124c2b885505c0c8a1f6d8573 (MD5) Apendice1_Perfil_Sensorial_.pdf: 298186 bytes, checksum: e335ad0c560e45bfdcd3661514ee45a1 (MD5) Apendice2_Checklist.pdf: 231707 bytes, checksum: 43db93b883f38b8d49ff0ceb264dd45d (MD5)